La fiesta de navidad de la cultura indígena Saraguro, como motivación para representación pictórica, con una visión del cubismo analítico - Quizhpe Quizhpe, Darwin Alfonso (2015)
This research has as main objective to analyze the cultural context of the holidays of the Saraguro ethnicity and thus support the pictorial representation of scenes, events, rituals that occur in the course of the party, taking into account the vanguards XX century, such as the analytical cubism. Therefore this subject, for painting is a challenge and at the same time, motivation to ennoble or strengthen the culture and art of Saraguro, otherwise whether that ethnicity is not valued, will undergo radical changes or perhaps disappear. As this theoretical research project - practical, various techniques and methods, such as enabling analytical analysis and interpretation of the information obtained, are used by biographical documents, books, magazines, etc. and techniques and instruments such as interviews, videos, photographs and direct observation of the medium and thus systematize, selecting ideas, compositions for a series of preliminary sketches to capture the paintings. Thereby obtaining satisfactory and interesting results, because through the analytical cubism reveals an entirely contemporary vision of this celebration, yet keeping with neatness and care schemes that make this pictorial trend, as some Latin American artists will They have time ago. The paintings are full of color, shapes and movement, as the party is presented in this way; the beauty of its colorful costumes, dances, are reflected through the imaginary des configuration and rebuild laps through geometric shapes and deformations of the characters. With these paintings the artist tries to leave embodied in canvasses their experiences and traditions